An Auditory Vigilance Task for Mental Fatigue Detection - Pang, Y.Y.; Li, X.P.; Shen, K.Q.; Zheng, H.; Zhou, W.; Wilder-Smith, E.P.V. (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2005)
An auditory vigilance task (AVT) as a validation criterion for monitoring mental fatigue was proposed in this study. The biological basis of this task design is on the understanding that mental fatigue is a cortical deactivation. This AVT is simple to perform, free of learning curve and independent on acquired skills (aptitude, knowledge). The validity and sensitivity of this task was verified by a scientifically controlled 25-hour fatigue experiment recorded by electroencephalogram (EEG). Results showed that this AVT is highly sensitive to changes during fatigue process. The effectiveness of this AVT was compared to one subjective rating scale (FSS). The 5-level fatigue EEG datasets (labeled by AVT and FSS respectively) were fed into support vector machines (SVM). SVM test accuracy indicated that AVT is more effective than subject's own estimation. The results demonstrate conclusively that this AVT is suitable for fatigue detection study as a reliable validation criterion